Metodika opredeleniya biomechanicheskikh pokazatelei s ispol'zovaniem personal'nogo kompyutera - Sannikova, N. I. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
With the occurrence of personal computers and software the favorable opportunities to use them in an educational process and in the educational course "Biomechanics" were created. The definition of biomechanical parameters was carried out by the results of videoshooting of running. The videocamera was put at the height of 140 sm, it stood on the distance of 22 meters from the line of an athlete's movement. The additional illumination was used. On one half of the body in the characteristic points of an athlete the markers by the size 3?3 sm were put. The materials of videoshooting were digitized and entered into the personal computer. Using the available software, Adobe Photoshop, Auto Cad, Microsoft Excel, it is possible to calculate biomechanical parameters of sports motor activity, to take more complete information on quantitative structure of movement.